Extension and Advisory Services by Milk Producer Organizations in Andhra Pradesh -Satisfaction of Member Producers - Ragjni, G, Vijaya; B, Subrahmanyeswari (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Milk producer organisations (MPOs) are empowering milk producers with appropriate technical knowledge and skills. But, the intangible services such as knowledge provision through extension and advisory services (EAS) have been less valued by cooperatives and also by the dairy farmers. In this context, a study was carried out to know the statusof extension and advisory services provided by MPOs in terms of satisfaction of milk producers in Andhra Pradesh. Ex-post-facto research design was followed to study 180 milk producers who were selected from the three renowned milk producer organisations existing in Andhra Pradesh. The study revealed that majority of respondents were middle aged, illiterate, male, belong to open category and were members of co-operatives since years. Most of the milk producers were satisfied and partly satisfied with extension services, whereas milk producers in majority satisfied with advisory services from MPOs. However, it was found that MPOs were not making use of electronic and digital technologies for EAS. It is recommended that MPOs can make use of ICT tools such as television, mobile telephonyfor rendering timely extension advisory services to the member producers towards sustainable production.
Keywords: Extension and advisory services; Level of satisfaction of milk producers; MPOs; Milk producers